Loss of Cochlear Ribbon Synapse Is a Critical Contributor to Chronic Salicylate Sodium Treatment-Induced Tinnitus without Change Hearing Threshold - Wei Zhang; Zhe Peng; ShuKui Yu; Qing-Ling Song; Teng-Fei Qu; Lu He; Ke Liu; Shu-Sheng Gong (Neural Plasticity)
Tinnitus is a common auditory disease worldwide; it is estimated that more than 10% of all individuals experience this hearing disorder during their lifetime. Tinnitus is sometimes accompanied by hearing loss. However, hearing loss is not acquired in some other tinnitus generations. In this study, we injected adult rats with salicylate sodium (SS) (200 mg/kg/day for 10 days) and found no significant hearing threshold changes at 2, 4, 8, 12, 14, 16, 20, or 24 kHz (all p>0.05). Tinnitus was confirmed in the treated rats via Behaviour Testing of Acoustic Startle Response (ASR) and Gap Prepulse Inhibition Test of Acoustic Startle Reflex (GPIAS). A immunostaining study showed that there is significant loss of anti-CtBP2 puncta (a marker of cochlear inner hair cell (HC) ribbon synapses) in treated animals in apical, middle, and basal turns (all p<0.05). The ABR wave I amplitudes were significantly reduced at 4, 8, 12, 14, 16, and 20 kHz (all p<0.05). No significant losses of outer HCs, inner HCs, or HC cilia were observed (all p>0.05). Thus, our study suggests that loss of cochlear inner HC ribbon synapse after SS exposure is a contributor to the development of tinnitus without changing hearing threshold.